Unveiling the Enzymatic Degradation Process of Biobased Thiophene Polyesters - Bertolini, Federico A.; Soccio, Michelina; Weinberger, Simone; Guidotti, Giulia; Gazzano, Massimo; Guebitz, Georg M.; Lotti, Nadia; Pellis, Alessandro (Frontiers in Chemistry, 2021)
In the last 20 years, scientific research focused on the identification of valid alternatives to materials of fossil origin, in particular, related to the bio-based polymers field. Recently, the efforts led to the synthesis of thiophene-based polymers (TBPs), a new class of polyesters based on 2,5-thiophendicarboxylic acid (TPCA) that can be industrially produced employing biomass-derived molecules. In this study, TBPs were synthesized using diols with different chain length (from C4 to C6) leading to poly(butylene 2,5-thiophenedicarboxylate) (PBTF), poly(pentamethylene 2,5-thiophene dicarboxylate) (PPeTF) and poly(hexamethylene 2,5-thiophenedicarboxylate) (PHTF), respectively, that were processed to thin films. To investigate enzymatic hydrolysis of these polymer films, cutinase 1 (Thc_cut1) and cutinase 2 (Thc_cut2) from Thermobifida cellulosilytica were recombinantly expressed in the host E. coli and afterwards purified. After 72 h of incubation at 65 °C with 5 µM Thc_cut1, weight loss and HPLC analysis indicated 9%, 100% and 80% degradation of PBTF, PPeTF and PHTG with a concomitant release of 0.12 mM, 2.70 mM and 0.67 mM of TPCA. SEM analysis shows that tiny holes were formed on the surface of the films and after 72 h PPeTF was completely degraded. LC-TOF/MS analysis indicated that especially Thc_cut2 released various oligomers from the polymer during the reaction. In addition, FTIR analysis shows the formation of novel acid and hydroxyl groups on the polymer surfaces. The results show that the two used thermostable cutinases are promising biocatalysts for the environmentally-friendly degradation of TPCA-based polyesters, in view of a possible sustainable recycling of plastic waste through re-synthesis processes.